Keggin heteropolyacid supported on BN and C3N4: Comparison between catalytic and photocatalytic alcohol dehydration. (15th June 2020) - Pomilla, Francesca Rita; Fazlali, Farnaz; García-López, Elisa I.; Marcì, Giuseppe; Mahjoub, Ali Reza; Krivtsov, Igor; Liotta, Leonarda F.; Palmisano, Leonardo
Abstract: The Keggin heteropolyacid (HPA), H3 PW12 O40 (PW12 ) has been supported on commercial boron nitride (BN) and two types of home prepared carbon nitride (C3 N4 ). The supported PW12 was used in the gas-solid (photo)catalytic 2-propanol dehydration reaction to give propene at atmospheric pressure and temperatures in the range 70–120 °C and resulted more active than the pristine PW12 . Reaction rate increased by increasing the temperature. Noticeably, the propene formation rate was higher by irradiating the catalytic system. The PW12 /BN material resulted more active than PW12 /C3 N4 . The acidity of the HPA cluster accounts for the catalytic role, whereas both the acidity and the redox properties of the HPA species were responsible for the increase of the reaction rate in the photo-assisted catalytic reaction.